Optogenetic/Chemogenetic Activation of GABAergic Neurons in the Ventral Tegmental Area Facilitates General Anesthesia via Projections to the Lateral Hypothalamus in Mice - Yin, Lu; Li, Long; Deng, Jiao; Wang, Dan; Guo, YongXin; Zhang, XinXin; Li, HuiMing; Zhao, ShiYi; Zhong, HaiXing; Dong, HaiLong (Frontiers in Neural Circuits, 2019)
The ventral tegmental area (VTA) reportedly regulates sleep and wakefulness through communication with the lateral hypothalamus. It has also been suggested that adequate anesthesia produced by administration of chloral hydrate, ketamine, or halothane significantly reduces the GABAergic neuronal firing rate within the VTA. However, the exact effects on GABAergic neurons in the VTA and the mechanisms through which these neurons modulate anesthesia through associated neural circuits is still unclear. Here we used optogenetic and chemogenetic methods to specifically activate or inhibit GABAergic neuronal perikarya in the VTA or their projections to the lateral hypothalamus (LH) in Vgat-Cre mice. Electroencephalogram (EEG) spectral analyses and burst-suppression ratio (BSR) calculations were conducted following administration of 0.8% or 1.0% isoflurane, respectively, and loss of righting reflex (LORR), recovery of righting reflex (RORR), and anesthesia sensitivity were assessed under 1.4% isoflurane anesthesia. The results showed that activation of GABAergic neurons in the VTA increased delta wave power from 40.0% to 46.4% (P=0.006) and decreased gamma wave power from 15.2% to 11.5% (P=0.017) during anesthesia maintenance. BSR was increased from 51.8% to 68.3% (P=0.017). Induction time (LORR) was reduced from 333 s to 290 s (P=0.019), while arousal time (RORR) was prolonged from 498 s to 661 s (P=0.007). Conversely, inhibition of VTA GABAergic neurons led to opposite effects. In contrast, optical activation of GABAergic VTA-LH projection neurons increased power of slow delta waves from 44.2% to 48.8% (P=0.014) and decreased that of gamma oscillations from 10.2% to 8.0%. BSR was increased from 39.9% to 60.2% (P=0.0002). LORR was reduced from 330 s to 232 s (P=0.002) and RORR increased from 396 s to 565 s (P=0.007). Optical inhibition of the projection neurons caused opposite effects in terms of both the EEG spectrum and the BSR, except that inhibition of this projection did not accelerate arousal time. These results indicate that VTA GABAergic neurons could facilitate the anesthetic effects of isoflurane during induction and maintenance, while postponing anesthetic recovery, at least partially through modulation of their projections to the LH.